Analisis Pelaksanaan Keselamatan Pasien oleh Perawat - Tria Harsiwi Nurul Insani; Sri Sundari (Universitas 'Aisyiyah Yogyakarta, 2018)
The aim of this study was to analyze the implementation of patient safety by nurses in this hospital. This type of research used in this study was mix methods with descriptive approach in quantitative data and content analysis approach in qualitative data. Sample of this study consist of 32 nurses for quantitative data with observation and 4 interviewees for qualitative data with in depth interview. Identification patient safety correctly 84%, effective communication 91%, improve the safety of high alert medications 100%, ensure safe surgery 100%, reduce the risk of health care associated infections 94%, reduce the risk of patient harm resulting from falls 81%.